Molecular docking analysis of thymoquinone as a potential inhibitor of C-reactive protein and transforming growth factor β (TGF-β): an in-silico study for myocardial infarction therapeutics - Muhammad Saugi Abduh; Ahmad Umar Alfaruq; Muh Adytia Prasada; Dimas Nabih (Medicinski glasnik, 2026)
Abstract Background: Myocardial infarction (MI) is a cardiovascular disease that is the leading cause of death at all ages. Inflammation and oxidation processes constitute the basic pathophysiology of MI development. C-reactive protein (CRP) and transforming growth factor ? (TGF-?) are markers that are often used to evaluate the level of inflammation, especially in MI. Objective: This study aimed to evaluate the anti-inflammatory potential of thymoquinone (TQ), the major bioactive compound of Nigella sativa, by assessing its binding affinity through molecular docking, in which TQ exhibited more favorable binding energies compared to the native ligand. Methods: Using the VegaZZ, PyMOL, and BIOVIA Discovery Studio tools, AutoDock Vina software was used for in silico research to test the active molecule TQ and produce visual profiles of native CRP and TGF-? ligands. Using the pkCSM method, pharmacokinetic predictions were carried out. Results: Thymoquinone (2-methyl-5-propan-2-ylcyclohexa-2,5-diene-1,4-dione) showed favorable binding affinity to both CRP and TGF-?, with docking scores of -3.60 and -4.15 kcal/mol, respectively, which are more favorable than those of the native ligands (-2.39 and -2.73 kcal/mol) and comparable to enalapril (-4.84 and -6.13 kcal/mol). The RMSD value for CRP was 1.421 Å, while the value for TGF-? was 0.253 Å, indicating excellent structural alignment and validating the docking approach. Conclusions: These in silico findings suggest that TQ warrants further investigation in vitro and in vivo as a potential modulator of inflammatory pathways in MI.
Keywords: anti-inflammatory agents; Enalapril; Molecular Docking; myocardial infarction; Thymoquinone